Investigasi variabel-variabel yang memengaruhi minat penggunaan QRIS oleh mahasiswa: financial literacy sebagai variabel moderasi - Wardani, Vindi Kusuma; Wardoyo, Cipto; Wulandari, Dwi (Jurnal Ilmu Manajemen, 2024)
This research investigates the factors influencing the use of the Quick Response Code Indonesian Standard (QRIS) among students in the Madura Region, focusing on the role of financial literacy as a moderator. The study utilises the Unified Theory of Acceptance and Use of Technology (UTAUT) framework with independent variables, including performance expectancy, effort expectancy, social influence, facilitating condition, and financial literacy as moderating variables. A quantitative research method is employed, collecting data through a survey using questionnaires from 400 higher education students in the Madura Region. The results of data analysis show that performance expectancy and facilitating conditions significantly influence student interest in using QRIS and can be moderated by financial literacy. Meanwhile, effort expectancy and social influence do not significantly affect behavioural intention and cannot be moderated by financial literacy. This research contributes to understanding the factors that influence QRIS adoption among students and emphasises the important role of financial literacy in using financial technology.